Assessment of serum survivin in women with placenta previa and accreta spectrum: a cross-sectional study - Nevin Yilmaz; Isil Turan Bakirci; Busra Sahin; Gokhan Bolluk; Esra Can; Huri Dedeakayogullari (Scientific Reports)
Abstract This study aimed to examine the relationship between maternal serum survivin levels and placental disorders by comparing these levels across cases of normal placentation, placenta previa, and placenta accreta spectrum (PAS). In this prospective cross-sectional study, we enrolled 84 pregnant women categorized into control (n = 42), placenta previa (n = 24), and PAS (n = 28) groups. Serum survivin levels were quantitatively determined using ELISA, and statistical analyses were performed using ANOVA and post-hoc tests. Serum survivin levels were significantly elevated in the placenta previa (348.3 pg/mL, range: 173.0-776.4) and PAS groups (785 pg/mL, range: 324.50–1122) compared to controls (177.9 pg/mL, range: 87.3–242.0) (p < 0.05), suggesting an association between survivin expression and abnormal placental adherence and invasion. Our findings demonstrate significant associations between elevated serum survivin levels and placental disorders, specifically placenta previa and PAS. These associations suggest a potential role for survivin in the pathogenesis of placental complications and warrant further investigation through longitudinal studies.